2011
DOI: 10.1097/jom.0b013e318236399e
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Occupational Hazards Related to Medical Lasers

Abstract: Because of the clinical benefits they provide, the growth of laser technologies and applications are anticipated to result in an increase in the number and type of medical personnel with future exposure to laser hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…For example, in the use of laser therapies, laser radiation absorption can result in thermal damage when the laser radiation raises the temperature of body tissue [50]. This type of exposure while performing laser procedures can result in eye injuries, which are the most common, as well as skin burns and electric shock.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the use of laser therapies, laser radiation absorption can result in thermal damage when the laser radiation raises the temperature of body tissue [50]. This type of exposure while performing laser procedures can result in eye injuries, which are the most common, as well as skin burns and electric shock.…”
Section: Resultsmentioning
confidence: 99%
“…Pierce (2011) reported on 37 cases of laser-induced injures to health care workers more broadly (e.g., technicians, laser operators, ancillary medical staff) which occurred while performing medical procedures; 73% caused eye injuries, some of which were permanent. Personal protective eyewear was not always worn and is essential in preventing direct and indirect beam exposure [50]. Also, it has been reported that radiation exposure can occur through exposure to urine and feces from patients treated with Radium-223 and Iodine-131 [51,52] which is a care task of NAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasers are second only to electrosurgery as the most common ignition source in operating room fires [64]. Lasers do not require direct contact with material to cause combustion.…”
Section: Laser Surgerymentioning
confidence: 99%
“…The dimension of laser‐induced tissue damage depends upon the wavelength and irradiance of the incident optical radiation, thereby determining the depth of penetration and severity of injury. Biological laser‐tissue interaction may be categorized as photo‐acoustic, photo‐chemical and photo‐thermal reactions . Q‐switched Nd: YAG 532‐nm laser is used for the treatment of vascular lesions and epidermal pigmented lesions because of its penetration depth and absorption spectrum in skin tissue .…”
Section: Introductionmentioning
confidence: 99%